Novel concepts for damage control resuscitation in trauma. Issue 6 (December 2017) - Van, Philbert Y.; Holcomb, John B.; Schreiber, Martin A.
Abstract : Purpose of review: Traumatic injuries are a major cause of mortality worldwide. Damage control resuscitation or balanced transfusion of plasma, platelets, and red blood cells for the management of exsanguinating hemorrhage after trauma has become the standard of care. We review the literature regarding the use of alternatives to achieve the desired 1 : 1:1 ratio as availability of plasma and platelets can be problematic in some environments. Recent findings: Liquid and freeze dried plasma (FDP) are logistically easier to use and may be superior to fresh frozen plasma. Cold storage platelets (CSPs) have improved hemostatic properties and resistance to bacterial contamination. Low titer type O whole blood can be transfused safely in civilian patients. Summary: In the face of hemorrhagic shock from traumatic injury, resuscitation should be initiated with 1 : 1 : 1 transfusion of plasma, platelets, and red blood cells with limited to no use of crystalloids. Availability of plasma and platelets is limited in some environments. In these situations, the use of low titer type O whole blood, thawed or liquid plasma, cold stored platelets or reconstituted FDP can be used as substitutes to achieve optimal transfusion ratios. The hemostatic properties of CSPs may be superior to room temperature platelets.